2001
DOI: 10.1155/2001/630972
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity in Cervical Smears

Abstract: It is well known that almost all carcinoma cells including those of the uterine cervix have re‐established their telomerase activity. However, until now there is no conclusive picture on the telomerase activity in cervical dysplasias and about their relationship to HPV infection. To investigate this question, material from 34 patients (15 with normal epithelium, 11 with LGSIL, 8 with HGSIL) obtained by conventional cervical brushing was used and subjected to non‐radioactive TRAP‐ELISA (Boehringer Mannheim). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Our results are comparable to previous studies in which hTERT expression relates to the severity of the disease [30][31][32]. [33,34]. Published studies on the subject reveal that hTERT expression and telomerase activity was reported in 91.3%, 96.5% and 100% of cervical cancer samples [35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…Our results are comparable to previous studies in which hTERT expression relates to the severity of the disease [30][31][32]. [33,34]. Published studies on the subject reveal that hTERT expression and telomerase activity was reported in 91.3%, 96.5% and 100% of cervical cancer samples [35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the inhibition of hTERT expression can trigger apoptosis before a significant effect on the mean telomere length is obtained. Similarly, it has been found that transfection-enforced overexpression of hTERT hTERT and mitochondrial cell death C Massard et al can reduce stress-induced cell death (Lu et al, 2001;Saretzki et al, 2001;Gorbunova et al, 2003;Luiten et al, 2003;Kang et al, 2004). According to one group, hTERT that lacks reverse transcriptase activity loses its cytoprotective activity (Zhang et al, 2003), but according to another group, hTERT mutants that lack telomerase activity still can suppress cell death induction, for instance by DNA-damaging agents (Rahman et al, 2005).…”
mentioning
confidence: 93%
“…In intraepithelial neoplasia, the occurrence rate is approximately 58%. 18 Kailash et al 19 studied 154 cervical tissue samples and observed a significant correlation (P G 0.01) between telomerase activity and positive results for HPV types 16 and 18. The authors also observed relatively high telomerase levels in high-grade lesions and invasive cervical carcinoma, which is similar to the findings of other authors.…”
Section: Discussionmentioning
confidence: 98%